OUT-OF-CLASS STUDIES FOCUS ON SOLVING PROBLEM AS A PREPARATION FOR OBMEP - Thiago Beirigo Lopes; Laila Cristina Frizon; Levi Manoel dos Santos (Instituto Federal de Mato Grosso, 2018)
A good classification in the Public-School Mathematics Olympiad (OBMEP) provides students, in addition to medals and honorable mentions, scientific initiation fellowships of the Junior Scientific Initiation (PIC). All this to intent students awaken to the taste and pleasure in studying mathematics and science in general, motivating them in the professional choice of scientific and technological careers. Therefore, was carried out the research project its objective is to analyze the contribution of the use of the Bank of Questions in the preparatory studies for the level 3 exam of the first phase of OBMEP. To this end, with the help of the two fellows, studies were carried out for two hours per week throughout the duration of the project from the perspective of George Pólya's problem solving. Initially, it was inhibited to use the resolutions of the Bank of Questions as an auxiliary to the study and subsequently had the use of it liberated for the questions that had not been resolved. With this study, were compared the results of the exams of 2016 and 2017 carrying out an analysis of these data and showing the vision of the fellows who were also individuals participating in the research.